The development of Site-Specific Tropical Fruit Management System (STroFMaS) model / Nur Sharain Abdul Rashid - Abdul Rashid, Nur Sharain (2006)
Precision Agriculture (PA) is a suite of information technology that can support a farm based and site-specific crop management system in agriculture production. It uses advanced information technologies to identify and evaluate temporal and spatial variation in cropland. This concept is used in developing the Site-Specific Tropical Fruit Management System (STroFMaS) model. This model combines the technology of site specific map and a tropical fruit management System. The tropical fruit industry is beset with two major problems: low yield of fruit trees and post harvest losses. Currently, there is no proper management in handling the tropical fruit production. The purposes of this research are to identify the user requirements in Site-Specific Tropical Fruit Management System (STroFMaS), to design an interactive map and a tropical fruit management system and to demonstrate the concept of PA. There are several methods and procedures used in this research. There are observations, interviews and document reviews. In order to support the procedures, requirement and data analysis are done. The release of STroFMaS introduces the new paradigm in tropical fruits management.